The antioxidant capacity of pumpkin seed oil and its impact on the stability of heated sunflower oil - Haylana Mostafa Al-Turky; Maysoon Alhafez; Basel Ibrahim (Results in Chemistry)
Pumpkin seeds are considered to be agricultural residues locally, which can be utilized as a source for extracting vegetable oil. This study aims to determine tocopherols and total carotenoid contents and to evaluate the antioxidant capacity of two species of pumpkin (Cucurbita Maxima and Cucurbita Moschata) seed oils. An estimate of the efficiency of the extracted oil on sunflower oil protection against oxidative deterioration was conducted during 32 h of heating at 180 ± 5°C. The DPPH and ABTS assay results showed that C.Maxima seeds oil exhibited a greater free radical scavenging capacity. C.Maxima seeds oil was rich in tocopherols (1433.637 mg/kg oil), especially of γ-tocopherol. In comparison, C.Moschata seeds oil was characteristic of a high carotenoid concentration (44.843 mg of β-carotene/kg oil). Adding 10 % of C.Maxima seeds oil to sunflower oil may delay its lipid oxidation by minorly increasing its peroxide and acid values and reducing its iodine value compared to untreated sunflower oil.